Future e+e− linear colliders ‐ physics motivation and physics reach. Issue 1 (29th October 2015) - Yamamoto, Hitoshi
Abstract : The discovery of the Brout‐Englert‐Higgs boson by the LHC opened a new era of particle physics, and the scientific case for the International Linear Collider (ILC) has become ever more compelling. The measurement accuracies of the Higgs couplings are such that one ILC is typically equivalent to 100 ultimate upgraded LHC's running simultaneously. Furthermore, if a new particle is within the energy reach of the ILC, the ILC would be able to find it even when the LHC has difficulty detecting it. We briefly over view the physics capability of the ILC. Abstract : In this article, the physics reach of e + e − linear colliders in the new era opened by the discovery of the Higgs particle is reviewed. Important features that make the linear colliders attractive are summarized and their key performances are compared to those of the upgraded High‐Luminosity LHC.